ANALISIS SISTEM INFORMASI MANAJEMEN TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA KANTOR KECAMATAN KADIA KOTA KENDARI - Putrianingsi, Eka; Tawai, Adrian; Liwaul, Liwaul (REZ PUBLICA, 2020)
The purpose of this study was to determine the management information system at the Kendari City Kadia sub-district office and to determine the effectiveness of the work of employees at the Kendari City Kadia sub-district office. The research methodology used in this study is a descriptive method that seeks to describe the intended phenomenon. The data obtained from the results of interviews with informants are 3 people directly involved in implementing the implementation of management information systems on employee work effectiveness. Then the data obtained is then analyzed and then interpreted and drawn a conclusion. The results of this study are based on the results of the analysis and discussion that have been voiced, that the Analysis of Management Information Systems on Employee Work Effectiveness at the District Office of Kadia Kendari that the management information system consists of functionality, professionalism and quality. Then the effectiveness of employee work consists of productivity, motivation and work environment.